Thermal energy storage materials designed from recycled Tetra Pak waste and paraffin waxes with enhanced photothermal conversion efficiencies - Safna Nishad; Mabrouk Ouederni; Igor Krupa (Energy and Built Environment)
The phase change material (PCM)-integrated solar water heaters have great potential to save energy by utilizing renewable resources and to extend working hours even after sunsets. The PCM composites fabricated with recycled waste products lead to the circular economy which would contribute significantly to the sustainable development goals. In this work, Tetra Pak waste (TP) was used to prepare a form-stable PCM composite by mixing with paraffin wax (PW) and expanded graphite (EG) to integrate with solar water heaters. Two different PWs with melting points of 44 (RT44) and 64 (RT64) were used in the lower and higher temperature ranges of domestic water heating applications, respectively. The prepared composites exhibited enhanced thermal conductivity (1.1–1.15 W/m °C), heat storage capacity (98.5–105.6 J/g), and photothermal conversion efficiency (85 % and 55 % for composites with RT44 and RT64, respectively). The numerical analysis conducted on a validated model helped to estimate the optimum composite thickness for specific solar exposure time. The fabricated PCM composite promoted the recycling of TP waste into useful products and was efficient in maintaining a higher nocturnal water temperature in the solar water heater.